Effect of 1-MCP on storage life, quality and antioxidant enzyme activities of broccoli - WANG Qiao-mei; KyiKyiWin (浙江大学学报. 农业与生命科学版)
Broccoli florets were treated with 1-methylcyclopropene (1-MCP) at concentrations of 0-5.0 μL/L for 6 h at 20 C followed by storage at 20℃. 1-MCP markedly extended the storage life and delayed the degradation of chlorophyll. The beneficial effects were dependent upon concentrations, and 2.5 μL/L 1-MCP was the most effective one among all the treatments, the contents of vitamin C and protein in this treatment were always higher than those in the control during storage at 20 C. SOD and CAT activities were higher while POD activity was lower in the treatment than in the control.